In Praise of Illusions: Giacomo Leopardi‘s Ultraphilosophy - Geir Sigurðsson; Geir Sigurðsson; Geir Sigurðsson (Nordicum-Mediterraneum, 2010)
Judging from his most prominent works, the Italian poet and writer Giacomo Leopardi (1898-1937) may seem to have been a rather isolated proponent of classical thinking in his backward Recanati during Europe‘s powerful thrust to modernity. However, his philosophical diaries, Zibaldone di pensieri, written between 1817 and 1832 while not published until 1898, reveal that Leopardi followed closely the philosophical development in Europe during his time. By leaning on the chronologically ordered Zibaldone, as well as on some of his philosophical prose and essays, this paper seeks to clarify Leopardi‘s critical stance vis-a-vis the modern and scientific philosophy of the Enlightenment and formulate his own responses to the radically altered worldview with which it is associated. Leopardi predates both Friedrich Nietzsche and later existential thinkers in considering the scientific and epistemological advances in Europe to have brought about a collapse of meaning and significance for the human being and his status in the universe. While identifying, in a most lucid manner, the ills of modernity for meaningful human orientation, he at the same time proposes a way out of the ‘nothingness of being’ that involves a formulation of a new kind of philosophy – an ‘ultraphilosophy’ with the ability to overcome the negative effects of the modern philosophy while, nevertheless, accepting its most important and inevitable conclusions. In this endeavour, Leopardi offers an interesting and often entertaining discussion of the different propensities in Southern and Northern cultures to romantic sensitivity, the quest for truth and belief in social values.